TRANSFORMASI SISTEM PENGELOLAAN KEUANGAN ORGANISASI KEMAHASISWAAN - Aris Setiawan Karim; Luqmanul Hakiem Ajuna; Sri Dewi Yusuf (Jurnal Ilmiah Global Education, 2023)
This study aims to examine the phenomenon of student organization financial management at IAIN Sultan Amai Gorontalo. This study uses a qualitative method with a case study approach to student organizations at IAIN Sultan Amai Gorontalo while the research is starting from the process of planning, organizing, supervising and reporting accountability. This phenomenon finds answers, namely the financial management of student organizations is not well organized, the campus provides the potential for student organizations to commit fraud resulting in organizational disorientation starting from cheating during the implementation process, manipulation of accountability reporting, as well as the potential for TGR (claims for compensation) against students.